Evaluación radiográfica y microscópica de la acción de quelantes en la remoción del barro dentinario - Guevara Canales, Janet Ofelia (2014)
ABSTRACT Introduction: as part of endodontic treatment, root canals are cleaned and shaped, since shavings of dentin and organic materials, such as microorganisms, resulting from the action of instrumentation, create the so-called dental smear. Objective: carry out an in vitro evaluation of smear layer removal and dentinal tubule density reduction using chelating irrigation solutions. Methods: an experimental study was conducted for which 30 single-rooted human teeth were selected after initial radiographic examination to verify the presence of a single canal, absence of calcification, internal resorption and endodontic treatment either completed or underway. Next, instrumentation was performed with three different irrigation solutions: 17 % ethylenediaminetetraacetic acid, 10% citric acid and 5.25% sodium hypochlorite (control group). Each instrumented tooth was then evaluated radiographically using a density scale made of aluminum with different density markers. Scanning electron microscope analysis was performed on three teeth from each group, which were treated with different irrigation solutions. Seven teeth from each group were infiltrated with methylene blue to determine marginal infiltration under the stereomicroscope. The teeth were evaluated on their three thirds: cervical, middle and apical. Results: radiographs did not reveal any statistically significant difference between the mean densities of the different groups of teeth in all thirds. Scanning electron microscopy showed a statistically significant difference between the three groups of irrigation substances (p < 0,001), with greater smear layer removal from the cervical third. Optical microscopy showed that infiltration was greatest in the ethylenediaminetetraacetic acid group, followed by the citric acid group, and lowest in the control group. Conclusion: analysis of radiographic and microscopic density revealed that except for the control group, chelating agents were efficient in removing dental smear. None of the substances showed any alteration in the radiographic density of dentinal tubules.